The Role of MRI in Breast Biopsy: A Comprehensive Analysis of Diagnostic Accuracy, Techniques, and Clinical Outcomes (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Breast cancer remains one of the most prevalent malignancies affecting women worldwide. Magnetic Resonance Imaging (MRI) has emerged as a pivotal tool in the diagnostic workup of breast lesions, particularly in cases where mammography and ultrasound yield inconclusive results. This paper aims to provide a detailed analysis of the role of MRI in breast biopsy, focusing on its diagnostic accuracy, various techniques employed, and the clinical outcomes associated with its use. We present expanded tables summarizing key findings from recent studies, highlighting the advantages and limitations of MRI-guided breast biopsy.